Effects of endopeptidase inhibition on the relaxation response of isolated human penile erectile tissue to vasoactive peptides. (6th April 2016) - Rahardjo, H. E.; Reichelt, K.; Sonnenberg, J. E.; Sohn, M.; Kuczyk, M. A.; Ückert, S.
Summary: Peptides, such as CNP, CGRP and VIP, are involved in the function of male penile erectile tissue. Tissue levels of said peptides are controlled by the endopeptidase enzymes. Theoretically, the inhibition of the degradation of CNP, CGRP and/or VIP should result in an enhancement in penile smooth muscle relaxation. The effects were investigated of CNP or VIP (0.1 nm –1 μm ), without and following pre‐exposure of the tissue to a threshold concentration of the endopeptidase inhibitor KC 12615 (10 μm, for 20 min), on the reversion of tension induced by means of electrical field stimulation. Drug effects on the production of cyclic AMP/GMP were also evaluated. Neither KC 12615, CNP and VIP nor the combination of CNP plus KC 12615 or VIP plus KC 12615 increased the response of the tissue to EFS. While no effects were observed of a pre‐exposure of the tissue to KC 12615 on the production of cyclic AMP in the presence of VIP, an enhancement was registered in the accumulation of cyclic AMP in the presence of CNP plus KC 12615. Further studies are indicated to investigate whether endopeptidase inhibitors might tend to be more effective in tissues affected by a decreased local production of vasoactive peptides.